Muscle ultrasound to diagnose sarcopenia in chronic kidney disease: a systematic review and bayesian bivariate meta-analysis - Qinbo Yang; Chen Zhang; Zhuyun Zhang; Baihai Su (BMC Nephrology, 2024)
Abstract Objective The aim of this systematic review was to assess the diagnostic test accuracy of muscle ultrasound for sarcopenia among chronic kidney disease (CKD) populations. Background Sarcopenia has become a worldwide health issue, especially for CKD patients. Conventional techniques of muscle mass assessment often prove limited, thus prompts increasing interest in ultrasound suitability. Methods We searched the Cochrane Library, PubMed and Embase for literature published up to June 2023. Ultrasound diagnosis of sarcopenia in CKD patients was included. Two independent investigators used the Quality Assessment Tool for Diagnosis Accuracy Studies (QUADAS-2) to assess the quality. We extracted valuable information from eligible studies. Using a Bayesian bivariate model, we pooled sensitivity and specificity values and summary receiver operating characteristic (SROC) curves. Results Five articles, involving 428 participants at various stages of CKD were included. Three studies diagnosed by the cross-sectional area (CSA) of the rectus femoris, while two others by muscle thickness (MT) and shear wave elastography (SWE) from the same muscle, separately. Overall, CSA or SWE had a pooled sensitivity of 0.95 (95% CrI, 0.80, 1.00), and the specificity was 0.73 (95% CrI, 0.55, 0.88) for diagnosing sarcopenia in CKD patients. Conclusions Ultrasound measurements of CSA and SWE were more sensitive for diagnosing sarcopenia in the CKD population than in the general population. Ultrasound assessment from a single peripheral skeletal muscle site may serve as a rapid screening tool for identifying sarcopenic individuals within the CKD population, if a specific cut-off value could be determined.